Building a rule-based goal-model from the IEC 62304 standard for medical device software - Kim, Dong Yeop; Lee, Byungjeong; Lee, Jung Won (KSII Transactions on Internet and Information Systems, 2019)
IEC 62304 is a standard for the medical device software lifecycle. Developers must develop software that complies with all specifications in the standard for licensing. However, because the standard contains not only a large number of specifications, but also domain-specific information and association relationships between specifications, it requires considerable effort and time for developers to understand and interpret the standard. To support developers, this paper presents a method for extracting the contents of the IEC 62304 standard as a goal model, which is the core methodologies of requirements engineering. The proposed method analyzes the grammar of the standard to robustly extract complex structures and various information from standard specifications and define rules that extract goals and links from syntactic element units. We validated the actual extraction process for the standard document experimentally. Based on the extracted goal model, developers can intuitively and efficiently comply with the standard and track specific information within the medical software and standard domains.
Keywords: Domain-specific information; Extraction process; Goal modeling; IEC 62304; Medical Devices; Software life cycles; Specific information; Standard specifications; Goal Model; IEC 62304; Medical Device; Requirements Engineering; Software